Study of electromagnetic solitons excited by different profile pulses - Aparna Sharma; Hitendra K. Malik; Harish Kumar (Journal of Theoretical and Applied Physics)
Abstract In the present paper, we see the effect of shapes of perturbing pulses on the evolution of electromagnetic solitons in a plasma having nonrelativistic ions and electrons. For this, we make use of IMEX scheme in our simulations, which is an invariant scheme for the two-fluid plasma flow equations. In particular, the impact of ion-to-electron mass ratio, electron-to-ion temperature ratio and the width of perturbing pulse is examined on the phase velocity, peak amplitude and width of the solitons.